“We Are Bridges”: Bilingual Latina Teachers as Cultural Mediators in Family–School Partnerships - Emma Chen (Education Sciences)
This paper explores the critical role of bilingual Latina educators as cultural mediators in fostering inclusive and effective parent engagement within schools. It calls for a shift from traditional, deficit-oriented approaches to parent engagement towards a strengths-based model that recognizes the valuable knowledge and contributions of families and for the incorporation of parent engagement courses in teacher education to better prepare educators for this critical work. Drawing from teacher reflections, this paper examines the unique ways in which these educators navigate cultural, linguistic, and systemic barriers to create spaces where Latinx families feel seen, heard, and valued. This paper highlights four key themes: (1) the role of bilingual educators as cultural and linguistic translators, (2) the challenge of reframing the deficit-based perspectives of Latinx families, (3) the importance of relationship-building through home visits, and (4) the emotional labor involved in advocating for marginalized families. Through these reflections, this paper advocates for systemic changes, emphasizing the need for formal institutional support for bilingual educators. It concludes by urging schools to adopt flexible, culturally responsive strategies that build long-term partnerships between educators and families.